Statistical analysis of the effects of disruptive factors of driving in simulated environment - Pauer, Gábor; Sipos, Tibor; Török, Árpád (Transport, 2019)
Distracting activities (such as using mobile phones, writing text messages) become increasingly common with the widespread use of telecommunication devices, becoming an increasing problem of road safety. Our research aimed to show the effects of these disruptive factors on driving. To quantify the effects, simulator tests have been performed. To analyse the significance of the changes caused by the disruptive factors, mathematical-statistical methods have been applied and conclusions for all drivers have been drawn. The effects of the disruptive factors have been quantified. On the one hand, the cognitive distraction and the hindrance of movements affects negatively the road safety, and on the other hand results in negative environmental and economic effects. Based on the numerical results of the research, hitting speeds caused by the disruptive factors have been determined as an example. The results of the research can be used as input data for the quantification of economic and environmental effects of road safety caused by disruptive factors and for the establishment of the background of legislation related to the prohibition of these factors.